Unveiling the Green Truth : How Transparent Are Malaysian Manufacturing Companies About Their Carbon Footprint - Khairunnisa, Ibrahim; Mohamad, Jais; Abu Hassan, Md. Isa; Muhammad Adzlan Syah, Ahmad Jaffary (Macrothink Institute, 2024)
Environmental sustainability has become a key concern for businesses worldwide, with expectations that they take responsibility for their carbon emissions and environmental effects.Reducing carbon emissions is critical for businesses due to companies' regulatory pressures and market expectations. Malaysia increased its mitigation ambition with an unconditional target to cut carbon intensity against GDP by 45% by 2030 compared to 2005 levels. This study aims to evaluate the extent of carbon footprint disclosure among manufacturing companies in Malaysia. Companies listed in Bursa Malaysia were chosen as the sample data in this study. The result of content analysis, approximately 18.97%, 269 of respondents are willing to disclose their carbon footprint information, suggesting a relatively low level of carbon footprint reporting. The policymakers should provide incentives for investment in green technology and enact strict regulations to encourage more companies to engage in carbon reporting.